EXPLORING THE POTENTIAL: A COMPREHENSIVE ANALYSIS OF THE TAPIOCA MICRO FOOD PROCESSING INDUSTRY IN SALEM DISTRICT, TAMIL NADU - Bharathi, Venkatesa Palanichamy Narasimma; Muthuswamy, Kalpana; Natarajan, Balakrishnan; Vasudevan, Balamurugan; Appavu, Suresh; Marimuthu, Rajavel; Rajaram, Dhivya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Tapioca, a key crop in Tamil Nadu, could support sustainable growth in micro food processing enterprises in the Salem district. The district accounts for 12% of the state's area and produces 13.36% of the state's sago, with high-quality starch production. Micro food processing businesses in the Salem district contribute to the local economy, providing employment and contributing to overall growth. The study revealed district is dominated by processing unit owners over 50 years old, with 20% owned by women and 80% by men. Most processors have 21-30 years of experience and belong to nuclear families. New mechanical methods have increased efficiency in making sago and extracting starch. Sago processing units in Salem face challenges such as equipment shortage, labor scarcity, loan availability, price fluctuations, quality deterioration, and drying issues. Most processing unit owners prefer to market their products through Channel III, which includes Farmer, Processor, Sago-serve, Trader, Wholesaler, and Retailer. The majority sell their products to Sago-serve Cooperative Society Ltd in Salem. Investing in infrastructure and supporting small-scale food processing enterprises is crucial for promoting economic growth and development in the district.